Low support level for S.League in Singapore : myth or reality? - Nur Syazana Mohd Taha (2011)
The Singapore League or S.League is the first professional football league in the country. Despite Singapore being a “football-mad country”, the support level for the S.League has been low. The purpose of this study is to verify and to identify reasons for the low level of support for the S.League. This study is conducted in two phases: the exploratory and descriptive phase. The first phase focuses on gaining some insights of the league. In the second phase, a quantitative approach is undertaken to analyze the low level of support for the S.League and its determinants. Both phases have confirmed the low level of support for the S.League. Furthermore, the four factors which have been identified as possible explanatory factors influencing the low support include „Attractiveness and Social Influence‟, „Perceived Brand Globalness‟, „Attachment with Players and Teams‟ and „Awareness of Players and Teams‟. The Football Association of Singapore and the S.League teams can utilize the result of this study to formulate their marketing strategies to attract fans.